Charged polymer membrane processing and its impact on membrane separation - Kim, Kyoungmin; Hallinan, Daniel T. (Frontiers in Membrane Science and Technology, 2025)
This review focuses on charged polymer membranes motivated by their growing importance in membrane-based separation technologies. Charged polymers have a long history in ion exchange chromatography, and thus charged polymer membranes are commonly termed ion-exchange membranes (IEMs). IEMs can be used in energy-efficient reverse osmosis desalination and are being studied for recovering valuable minerals from aqueous waste streams. Types of IEMs are first introduced, categorized by charge type, charge distribution and porosity. Synthesis of charged polymers is briefly discussed. Considerable attention is given to important membrane properties and methods for characterizing them. These properties include ion-exchange capacity (IEC), water content, structure, ionic conductivity, permeability, selectivity, and thermal and mechanical properties. A key challenge in membrane design is achieving high IEC, which is desired for high IEM selectivity. This is a challenge due to the high water uptake that accompanies high IEC. Relevant aspects of membrane structure include percolated ion channels, porous morphology and inert mechanical reinforcement phases. Membrane structure is essential in addressing the challenge of achieving high IEC and optimizing membrane performance. Structure is predominantly dictated by membrane processing. Thus, membrane processing methods, their benefits and drawbacks and their impact on structure are described in detail. These methods include solution casting, the paste method, extrusion, electrospinning, phase inversion, and an emerging method to form a composite IEM. Finally, specific IEM applications are discussed that hold great promise for circular economies. These applications include lithium extraction from battery waste, mining of desalination brine, and mineral recovery from semiconductor waste. A major driver for the growing interest in these applications is the demonstrated cost-effectiveness of membranes in commercial desalination. With on-going research advances, such success is probable in these extraction and recovery applications.